The Patisserie Competition: evaluating, assessing, & working together for the Pastry Department / Siti Rohimi Mohamed Apandi ... [et al.] - Mohamed Apandi, Siti Rohimi; Azmi, Nur Nadhirah; Ismail, Anida; Bibit, Nur Syahira (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
On July 10, 2023, students from the Faculty of Hotel and Tourism Management’s Permatang Pauh Campus hosted the annual Patisserie Competition in kitchens K2 and K3. The Pastry Department lecturers who taught Sugar Artistry and Petit Four (HTP282) organized the event. All Diploma in Pastry Arts students from semester 4 participated in this competition to exhibit their talents and inventiveness in the field of pastry arts. The event also gave these budding pastry students a chance to showcase their talents and earn some well-deserved credit for their efforts. The practical exam that is a part of the course requirements was the focus of the competition. The mission was to create a visually pleasing dessert buffet display for an assortment of sugar art and petit four goods. An array of different kinds of desserts from traditional ones to the new and exciting ones displayed in the competition. The purpose of the event was to provide students with a chance to demonstrate their creative abilities while also celebrating their accomplishments. The competition was judged by panels of external experts to eliminate any possibility of bias or prejudice towards the students, their ability, or their projects. A more objective assessment may result from this. Students showcased different curricula accumulated over the past semesters, and their participation in this competition displayed their art in baking beautiful pastries and desserts. The event, which honoured the creativity and expertise of pastry students, was a smashing success giving everyone involved not only a chance to shine but also an enjoyable time.